Effects of Urban Waste and Mineral Fertilizers Applications on Eucalyptus grandis Growth and Soil Conditions Efeito da Aplicação de Lixo Urbano Compostado e de Adubos Minerais no Solo e na Produtividade de Eucalyptus grandis - Guilherme de Castro Andrade; Antônio Francisco Jurado Bellote; Helton Damin da Silva; Renato Antônio Dedecek; José Luiz Lui Gava (Pesquisa Florestal Brasileira, 2011)
Forest plantations have been studied as a potential ecosystem able to absorb organic residues as fertilizers or soil conditioners. This study evaluate the effects of the application of composted organic waste and mineral fertilizers in a Eucalyptus grandis (W. Hill ex Maiden) plantation with 86 months of age in Neossolo Quartzarênico. It was analyzed wood production, litter decomposition and the physical and chemical changes in the soil properties. It was observed that the municipal composted organic wastes resulted in an increase of 45.6% in wood volume, as compared to the control. It also increase the velocity of the litter decomposition on average of 28% and 16% for leaves and twigs respectively, increasing the pH level values and the availability of water in the soil (from 13% to 25% more available water in the first layer of the soil, 0 -10 cm). As florestas têm sido estudadas como ecossistemas aptos à absorver resíduos orgânicos, utilizados como fertilizantes e condicionadores do solo. Este trabalho avaliou no Município de Itatinga, SP, em Neossolo Quartzarênico, os efeitos da aplicação de lixo urbano compostado e da adubação mineral em plantações de Eucalyptus grandis com 86 meses de idade. Foram analisadas as produtividades de madeira, a decomposição da serapilheira e as propriedades químicas e físicas do solo. Verificou-se que a aplicação de lixo urbano aumentou a produtividade de E. grandis com relação à testemunha, com um ganho de 45,6 % no volume cilíndrico de madeira. O solo com aplicação de lixo urbano apresentou um menor tempo de decomposição da serapilheira, em média com reduções de 28 % para folhas e de 16 % para galhos, com aumentos no pH e na água disponível no solo de 13 % a 25 %, na camada de 0 a 10 cm de profundidade, que podem justificar a maior produção de madeira obtida no final da rotação, em comparação com as parcelas que só receberam fertilizantes minerais.